Rod Shape Determination by the Bacillus subtilis Class B Penicillin-Binding Proteins Encoded by pbpA and pbpH - Wei, Yuping (American Society for Microbiology, 2003)
The peptidoglycan cell wall determines the shape and structural integrity of a bacterial cell. Class B penicillin-binding proteins (PBPs) carry a transpeptidase activity that cross-links peptidoglycan strands via their peptide side chains, and some of these proteins are directly involved in cell shape determination. No Bacillus subtilis PBP with a clear role in rod shape maintenance has been identified. However, previous studies showed that during outgrowth of pbpA mutant spores, the cells grew in an ovoid shape for several hours before they recovered and took on a normal rod shape. It was postulated that another PBP, expressed later during outgrowth, was able to compensate for the lack of the pbpA product, PBP2a, and to guide the formation of a rod shape. The B. subtilis pbpH (ykuA) gene product is predicted to be a class B PBP with greatest sequence similarity to PBP2a. We found that a pbpH-lacZ fusion was expressed at very low levels in early log phase and increased in late log phase. A pbpH null mutant was indistinguishable from the wild-type, but a pbpA pbpH double mutant was nonviable. When pbpH was placed under the control of an inducible promoter in a pbpA mutant, viability was dependent on pbpH expression. Growth of this strain in the absence of inducer resulted in conversion of the cells from rods to ovoid/round shapes and lysis. We conclude that PBP2a and PbpH play redundant roles in formation of a rod-shaped peptidoglycan cell wall.